Development of Science Learning Digital Media: Encyclopedia of Human Respirational Organs for Elementary School Student - Pastuti, Asti Wila; Iskandar, Rossi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
This research aims to determine the feasibility and effectiveness of products in digital encyclopedia learning media. Research and development use the Dick and Carrey development model which consists of 10 steps: (1) identifying objectives, (2) conducting instructional analysis, (3) analyzing students and learning contexts, (4) formulating performance goals, (5) developing assessment instruments, (6) developing instructional strategies, (8) designing and implementing formative evaluations, (9) teaching revisions, (10) designing and implementing summative evaluations. The results of research on digital encyclopedia learning media products developed have shown that: (1) media expert feasibility validation test gets a percentage of 74%; (2) linguist feasibility validation test gets a percentage of 90.91%; (3) material expert feasibility validation test gets a percentage of 90%; (4) product feasibility test by a small group gets a percentage of 78.58% and product effectiveness test gets 0,62; (5) the product feasibility test by a large group gets a percentage of 86.67% and the product effectiveness test gets 0,54. So it could be concluded that the digital encyclopedia as learning media could be applied in elementary school and it is effective for elementary school students.